Abdominopelvic Mass Revealing Tuberculosis in a Young Woman. (1st July 2021) - ELmajdoubi, Hicham; EL Yahiyaoui, Mariam; Baiss, Marouane; Bouzroud, Mohamed; Aboulfeth, El Mehdi; Najih, Mohammed; Bouchentouf, Sidi Mohamed; ELkaoui, Hakim; Bounaim, Ahmed
Abstract : Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and remains a health problem, especially in developing countries. Abdominal location represents 5 to 10% of all locations. The clinical symptoms are not very specific, and the discovery of an abdominal mass in a context of deterioration of general state may wrongly lead to the diagnosis of a tumor. Radiological explorations remain sensitive in the detection of abdominal masses but they cannot prejudge their etiology. Surgical exploration is sometimes the only recourse either for diagnostic purposes or complications, and the diagnosis can only be confirmed by bacteriological and histological examinations of the surgical specimen. We report the case of abdominopelvic mass and lymph nodes revealing tuberculosis.